1999
DOI: 10.1172/jci7317
|View full text |Cite
|
Sign up to set email alerts
|

A proinflammatory role for IL-18 in rheumatoid arthritis

Abstract: Figure 1(a) IL-18 mRNA was detected in RA and OA synovial membranes by RT-PCR (representative of 20 RA and 10 OA tissues). (b) Significantly higher levels of IL-18 were detected in RA SF than in sera (18 matched samples assayed after removal of rheumatoid factor).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
523
0
11

Year Published

2000
2000
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(556 citation statements)
references
References 44 publications
22
523
0
11
Order By: Relevance
“…The observed proinflammatory profile of IL-18 was first described in studies by Gracie et al 18 and Wei et al, 21 in which they demonstrated the pivotal role of IL-18 in the development of inflammatory arthritis. Other studies by Joosten et al 22,23 verified the importance of IL-18 in experimental arthritis through systemic neutralization of IL-18.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The observed proinflammatory profile of IL-18 was first described in studies by Gracie et al 18 and Wei et al, 21 in which they demonstrated the pivotal role of IL-18 in the development of inflammatory arthritis. Other studies by Joosten et al 22,23 verified the importance of IL-18 in experimental arthritis through systemic neutralization of IL-18.…”
Section: Discussionmentioning
confidence: 75%
“…Besides this systemic role of IL-18, it has been demonstrated that IL-18 is also produced in high amounts by the synovial lining of RA patients. 16,18 As a result of these high levels of IL-18 in local inflammatory processes intra-articular neutralization of IL-18 by adenoviral overexpressed IL-18BPc during onset of CIA could be effective. While control-treated mice developed a progressive inflammatory articular disease, Exogenous IL-18BPc ameliorates CIA RL Smeets et al intra-articular overexpression of IL-18BPc before clinical manifestation of the CIA resulted in amelioration of the arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negating the function of endogenous IL-18 with neutralizing IL-18 antibodies has also been effective in mouse models of hepatitis and Guillain Barrè syndrome [12,13]. Conversely, exogenously administered IL-18 exacerbates the course of type II collagen-induced arthritis and systemic lupus erythematosus-like syndrome in mice [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…12,22,23 Although some investigators have reported that RA patients have high concentrations of serum IL-18, 22 it is commonly accepted that IL-18 concentrations are higher in synovial fluid than in serum. 12 IL-18 would exert pathological effects only within affected synovium in RA, while systemic and abundant production of IL-18 would be specific for AOSD. These phenomena are consistent with the present data showing that a certain diplotype configuration is frequently observed only in AOSD.…”
Section: Il-18 Gene Polymorphisms In Aosd T Sugiura Et Almentioning
confidence: 99%